Ultra-low fertility in East Asia: policy responses and challenges*. Issue 2 (4th May 2019) - Jones, Gavin W.
ABSTRACT: In the countries of East and Southeast Asia where fertility has reached ultra-low levels, there has been a flurry of developments in pro-natalist policy over the past five years or so, but its impact appears to be limited. This paper addresses the strong obstacles hindering the success of pro-natalist policies in the region, suggests key interventions that are needed, and stresses that the policies in these countries should also be considering other ways of addressing the issues. Social policy has certainly moved ahead in positive ways in South Korea, Japan, and Taiwan, as evidenced by parental leave policy and childcare reform, but workplace cultures have yet to follow suit. The slow changes in gender norms, along with the pressures of educating children and finding housing in the big cities where most people in the region live, are the continuing realities facing couples considering marriage and childbearing.